2016
DOI: 10.1002/anie.201608219
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Range Hydrophilic Attraction between Water and Polyelectrolyte Surfaces in Oil

Abstract: The outstanding water wettability and the capability of polyelectrolyte surfaces to spontaneously clean oil fouling are determined by their wetting mechanism in the surrounding medium. Here, we have quantified the nanomechanics between three types of polyelectrolyte surfaces (i.e. zwitterionic, cationic, and anionic) and water or oil drops using an atomic force microscope (AFM) drop probe technique, and elucidated the intrinsic wetting mechanisms of the polyelectrolyte surfaces in oil and water media. The meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
97
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(98 citation statements)
references
References 50 publications
1
97
0
Order By: Relevance
“…Despite recent progress, there is little direct experimental evidence for the presence of the water film between the oil droplet and the substrate, and most previous discussions implicitly assume the presence of such a hydration layer. [7,8,11,12]. The thickness of this water film-should it exist-is not known and its relation to oil-repellency remains poorly understood.…”
mentioning
confidence: 99%
“…Despite recent progress, there is little direct experimental evidence for the presence of the water film between the oil droplet and the substrate, and most previous discussions implicitly assume the presence of such a hydration layer. [7,8,11,12]. The thickness of this water film-should it exist-is not known and its relation to oil-repellency remains poorly understood.…”
mentioning
confidence: 99%
“…[ 18–24 ] The zwitterionic polymers carry functional groups like carboxybetaine, sulfobetaine, phosphobetaine, etc., which have both positive and negative charge in the same monomer. [ 25 ] The strong polarity gives rise to a hydration layer around the zwitterionic polymer chains, [ 26,27 ] which can prevent the adsorption of oil droplets onto the polymer surfaces. [ 28 ] Studies have reported that copolymer hydrogels prepared by poly(ethylene glycol)diacrylate (PEGDA) and zwitterionic monomer, such as carboxybetaine methacrylate and sulfobetaine methacrylate (SBMA), demonstrate better hydrophilicity than those of PEGDA.…”
Section: Figurementioning
confidence: 99%
“…Recent interfacial force measurements have shown several interesting findings. Hayashi et al reported the presence of several nm-thick, repulsive layers near the bioinert oligoethylene glycol surfaces (Hayashi et al, 2012), and Shi et al demonstrated there is a long-range attraction between water and zwitterionic polymer brushes in oil (Shi et al, 2016). Further studies on the structures and dynamics of water in the vicinity of polymer/water interface potentially enable to overcome the commonly taken trial-and-error approaches toward the rational design, or even the prediction of new bioinert materials.…”
Section: Toward Rational Design Of New Materials: Bioinertnessmentioning
confidence: 99%